Nieve de agosto y otros poemas de Daniel Thomas Morán - Dreyfus, Mariela (2014)
Titled as August Snow and Other Poems, Peruvian poet Mariela Dreyfus introduces us to the poetry of Daniel Thomas Moran, who was born in New York in 1957.